HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMAMPUAN SOSIALISASI ANAK RETARDASI MENTAL RINGAN DI SLBN 1 BANTUL YOGYAKARTA 2015 - Redi Iriawan; Nurhidayat Nurhidayat; Aris Budi Pratama (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2016)
ABSTRACTIntroduction: Mental retardation is a condition that requires special attention, because in children with mental retardation experience limitations in the functioning of him so that it would interfere with the normal adaptation to the environment. Usually there is a child’s mental  evelopment is less overall, but the main symptoms are prominent intelligence is underdeveloped. With this, at least the family into the media in helping children with mental retardation in conformity with the  nvironment in line with vulnerable life. Family involvement is important in the process of socialization. Families provide support in order to receive all the advantages and disadvantages of the child, so that children can socialize and communicate with others and can develop the full potential of these limitations are optimaOobjectives: To determine the relationship of Family support wit social skill of child retardation mental in SLBN 1 Bantul YogyakartaMethods: Usingan instrument with a questionaire given to the families and childs with middle retardation mentals.Results: Family support is provided in the high category 18(36%) and in the middle category 24 (48%),  while Socials skill of Childs low retardation mentals in the category of  36 (72%) and 14 (28%) child’s have social skill is Less, besides, the results of this study showed ther is signiﬁ cant correlation between family support with socials skill of child retardation in SLBN 1 Bantul YogyakartaConclusion: There Is A Signiﬁ cance Relationship Between Two Variables Is Family Support With Socials Skill Of Retardation Mental Of Child At SLBN Bantul